PERSPECTIVES AND LIMITS OF MANDIBULAR LATERAL INCISOR INTRUSION ASSOCIATED WITH PERIODONTAL DISEASE. A FEM STUDY - Ionut Luchian; Mihaela Moscalu; Ioana Martu; Ioana Vata; Cristel Stirbu; Daniel Olteanu; Liliana Pasarin; Maria Alexandra Martu; Sorina Solomon; Diana Anton; Silvia Martu (Romanian Society of Oral Rehabilitation, 2019)
Introduction. FEM is a reliable tool for researching the impact of orthodontic therapy on the affected periodontal tissues. Material and methods. Using Catia V5R16 and Abaqus software we analysed various clinical scenarios for intruding the lateral mandibular incisor in different situations of horizontal bone loss (HBL). Results and Discussions. When intruding the lateral mandibular incisors we noticed that the equivalent tensions are increasing together with the extent of HBL and the magnitude of the applied force. Conclusions. When optimal intrusive forces are applied at the level of the mandibular lateral incisor, the periodontal status of the patient will not represent a restriction for the interdisciplinary treatment.